Research on the Seismic Performance of Prefabricated Bridge Piers Using UHPC Grout under an Eccentric Load - Ben Zeng; Jiahui Xu; Xiaohong Zheng; Songqi Zhang (Advances in Civil Engineering, 2023)
At present, research on prefabricated piers is limited to the axial compression state. However, many piers are under small eccentric compression in practical engineering. In this article, the seismic performance of ultrahigh performance concrete (UHPC)-grouted corrugated pipe-connected piers under small eccentric compression was studied. A pseudostatic test was carried out by using a prefabricated pier column model connected with UHPC-grouted corrugated pipes. The failure mechanism of the plastic hinge area of the column base was studied, and the failure mode, energy dissipation capacity, displacement ductility, and ultimate bearing capacity were compared with those of an ordinary axially compressed pier column structure. The result shows that compared to the conventional cast-in-place(CIP) pier, the overall energy dissipation capacity and the ductility factor of assembled pier with UHPC-grouted corrugated pipe-connection were decreased approximately by 5.0% and by 10%, respectively. The pinching phenomenon of the hysteresis curve of the precast pier was more obvious. When the assembled piers were under small eccentric compression, the overall energy dissipation capacity was close to that of conventional CIP piers and the ductility factor was improved by 20%. Comparison of two precast piers using the same UHPC grout connections shows that the stiffness degradation process of precast pier under small eccentric compression was similar to that under axial compression. But the ductility coefficient of precast pier under small eccentric compression increased by about 20%. The small eccentric compression caused different damage degrees in the plastic hinge zone at the bottom of the precast column. The ultimate load in the same direction as the additional bending moment was 55% lower than that of the opposite direction.